Aplikasi sinbiotik dengan sumber prebiotic berbeda pada udang windu - Adni Oktaviana; Dian Febriani (Departemen Akuakultur FPIK UNDIP, 2023)
Prebiotics are functional food fibers that have the potential to provide nutrients for gut microbes. The source of origin of prebiotics is one component of a material that can be claimed to be a prebiotic, and it affects the oligosaccharide content in it. This study will use synbiotics on tiger prawns with prebiotics from different sources. Synbiotics are a balanced combination of probiotics and prebiotics. The probiotic used was Lactobacillus sp bacteria, the prebiotic used was derived from coconut and sweet potato pulp, and the synbiotic used was dose 1 which consisted of 1%/kg probiotic feed and 2%/kg prebiotic feed. The experimental design used was a completely randomized design. This study consisted of three treatments with three replications. Treatment A (maintenance of tiger shrimp without the addition of synbiotic/control), Treatment B (maintenance of tiger shrimp with the addition of synbiotic with prebiotic source from coconut pulp powder), and Treatment C (maintenance of tiger shrimp with the addition of synbiotic with prebiotic source from sweet potato powder). Parameters observed were daily growth rate (DGR), feed convertion ratio (FCR), Total Haemocytes Count (THC), survival rate (SR) and water quality. The result from this study showed that B treatment give the highest growth and health parameters.